Expression pattern of microRNAs in ovine endometrium during the peri-implantation - Kose, Mehmet; Hitit, Mustafa; Kaya, Mehmet Salih; Kirbas, Mesut; Dursun, Sukru; Alak, Ilyas; Atli, Mehmet Osman (Elsevier BV, 2022)
MicroRNA (miRNA), acting as the transcriptional regulator of gene expression, has been widely demonstrated to be involved in many biological functions, including embryo implantation and development. The objective of the current study was to illuminate the expression pattern of microRNAs (miRNAs) in the endometrium during the peri-implantation in ewes. Intercaruncular endometrial samples was obtained from a total of 24 ewes on days of 12 (pre-implantation, n = 4), 16 (implantation, n = 4) and 22 (post-implantation, n = 4) of pregnancy following mating, and on their corresponding days of 12 (n = 4), 16 (n = 4) and 22 (n = 4) of the estrous cycle. The miRNA profiles were examined in the endometrium by microarray technology. We detected 116 ovine specifics miRNAs in the endometrium. Of these, nineteen were differentially expressed in early pregnancy. Four miRNAs (oar-miR-370-3p, oar-miR-411b-5p, oar-miR-379-3p and oar-miR-411a-3p) that had the most differential fold change were confirmed by RT-qPCR in ovine endometrium. The differentially expressed miRNAs targeted a total of 315 genes, resulting in 39 GO terms in molecular function, 353 in biological process, and 17 in the cellular component. The construction of the PPI network of target genes established two functional modules mostly enriched in the innate immune system, toll receptor cascades in module 1, whereas genes in module 2 were associated with GMCSF-mediated signaling events, insulin pathway, and mTOR signaling pathway. Based on the results, we may imply that miRNAs modulate ovine endometrium during the peri-implantation.
Keywords: Sheep; microRNA; Expression; Early Pregnancy; Microarray Analysis; Microrna; Ovine; Endometrium; MicroRNAs; Pregnancy; Animals; Female; Embryo Implantation; Sheep, Domestic